Efficient Detection of Structure and Dynamics in Unlabeled RNAs: The SELOPE Approach. Issue 23 (25th March 2018) - Schlagnitweit, Judith; Steiner, Emilie; Karlsson, Hampus; Petzold, Katja
Abstract: The knowledge of structure and dynamics is crucial to explain the function of RNAs. While nuclear magnetic resonance (NMR) is well suited to probe these for complex biomolecules, it requires expensive, isotopically labeled samples, and long measurement times. Here we present SELOPE, a new robust, proton‐only NMR method that allows us to obtain site‐specific overview of structure and dynamics in an entire RNA molecule using an unlabeled sample. SELOPE simplifies assignment and allows for cost‐effective screening of the response of nucleic acids to physiological changes (e.g. ion concentration) or screening of drugs in a high throughput fashion. This single technique allows us to probe an unprecedented range of exchange time scales (the whole μs to ms motion range) with increased sensitivity, surpassing all current experiments to detect chemical exchange. For the first time we could describe an RNA excited state using an unlabeled RNA. Abstract : Cheap and chic: SELOPE . Enabling the measurement of structures and dynamics with atomic resolution of unlabeled RNA samples. An unprecedented range of exchange time scales becomes accessible. The method allows for monitoring of structural changes in unlabeled nucleic acids samples for drug screening or interaction measurements.